2020
DOI: 10.1111/eva.12947
|View full text |Cite
|
Sign up to set email alerts
|

The three dimensions of somatic evolution: Integrating the role of genetic damage, life‐history traits, and aging in carcinogenesis

Abstract: Tumors result from genetic and epigenetic alterations that change cellular survival and differentiation probabilities, promoting clonal dominance. Subsequent genetic and selection processes in tumors allow cells to lose their tissue fidelity and migrate to other parts of the body, turning tumors into cancer. However, the relationship between genetic damage and cancer is not linear, showing remarkable and sometimes seemingly counterintuitive patterns for different tissues and across animal taxa. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The joint fluid CXCR4 expression levels of the control group were 3.05±1.11 and 2.13±0.63, and the joint fluid CXCL12 expression levels were 5.14±1.12 and 4.54±1.25. The present results suggested that CXCR4 and CXCL12 expression levels in the serum and articular fluid of the study group were significantly higher compared with the control group (P<0.05; Tables II and III [5][6][7][8].…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The joint fluid CXCR4 expression levels of the control group were 3.05±1.11 and 2.13±0.63, and the joint fluid CXCL12 expression levels were 5.14±1.12 and 4.54±1.25. The present results suggested that CXCR4 and CXCL12 expression levels in the serum and articular fluid of the study group were significantly higher compared with the control group (P<0.05; Tables II and III [5][6][7][8].…”
Section: Resultsmentioning
confidence: 69%
“…The pathogenesis of RA is complex, involving many types of cells, including macrophages, T and B cells, fibroblasts, chondrocytes and dendritic cells (4). Despite study into the role of many genes and mechanisms underlying the development of RA, there is still no clear predisposing factor (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of a species is a long-term process that shapes their neoplastic profiles [172]. Evidence showed that oncogenic tumors date back approximately 2 million years ago [95].…”
Section: Bc Is An Evolutionary Disordermentioning
confidence: 99%
“…[54][55][56] Recently, Laconi and colleagues proposed that, "the tumor-suppressive potential of youth is more potent than previously realized, limiting cancers through half a century of human life even in the face of increased DNA mutations and highly perturbed tissue environments," 57 and much additional work suggests that organismal aging and the associated development of cellular senescence, proinflammation, and waning immunity appear to be major mechanisms that allow for the development of these permissive environments. [58][59][60][61][62][63][64] Pathologically significant mutations are propagated during the process of DNA replication, as nondividing cells will not pass on the cancer phenotype to progeny cells.…”
Section: Cellular Replication and The Creation Of Aged (Permissive) M...mentioning
confidence: 99%